Redescription of Proisotoma ramosi Arlé, 1959 from Brazil (Collembola: Isotomidae) with designation of the neotype - de Mendonça, Maria Cleide; Abrantes, Eduardo Assis (Zootaxa, 2010)
Proisotoma ramosi Arlé is redescribed based on specimens collected for the first time at National Park of “Serra dos Órgãos”, Teresópolis, State of Rio de Janeiro. This species is easily identified by a set of characters: color white, 2+2 eyes, PAO long and narrow, labral setae pattern 4/554, external lobe of maxilla with bifurcate palp and 3 sublobal setae, sensillar pattern 53/22335 by half tergite, retinaculum with 4+4 teeth and two setae on corpus, manubrium with two anterior-distal setae, dens with 7 posterior and 11 anterior setae, mucro bidentate. Neotype for P. ramosi is designated.